Tranexamic acid evidence and controversies: An illustrated review - Nicole Relke; Nicholas L. J. Chornenki; Michelle Sholzberg (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Tranexamic acid (TXA) is an antifibrinolytic agent commonly used for the treatment or prevention of bleeding. Indications for TXA are diverse, including heavy menstrual bleeding, trauma, postpartum hemorrhage, traumatic brain injury, and surgical site bleeding. Despite decades of use and a robust body of evidence, hesitancy using TXA persists in many clinical settings. This illustrated review describes the history, pharmacology, and practical considerations of TXA use. We also describe the major landmark randomized controlled trials of TXA and their implications. Finally, we review the evidence around common controversies surrounding TXA such as the risk of thrombosis, prescription along with combined hormonal contraceptives, and use in patients with gross hematuria.